Guidelines for developing the management of learning Resources outside the school classroom in Wang Chao School Group Under the jurisdiction of Tak Primary Educational Service Area Office 1 - Panyamoon , Supakon; Yuttawong, Nontawat (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: study the current conditions and problems of out-of-classroom learning resource management in schools within the Wang Chao School Network under the Tak Primary Educational Service Area Office 1, and examine guidelines for developing out-of-classroom learning resource management in schools within the Wang Chao School Network under the Tak Primary Educational Service Area Office 1. The target group consisted of experts, school administrators, teachers, and educational personnel from schools in the Wang Chao School Network, totaling 138 participants. The research instruments included questionnaires and structured interviews. Data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The research findings revealed that: 1. the overall condition and each aspect of out-of-classroom learning resource management in the Wang Chao School Network were at a high level, while the most significant problems were found in the implementation of out-of-classroom learning resource utilization; and 2. the guidelines for developing out-of-classroom learning resource management included: (1) planning, in which school administrators should clearly define policies and directions for managing out-of-classroom learning resources; (2) implementation, in which school administrators or responsible personnel should continuously supervise and develop out-of-classroom learning resources and promote ongoing professional development;(3) evaluation, in which teachers and students should participate in evaluating the use of out-of-classroom learning resources; and (4) improvement, in which teachers should systematically analyze evaluation results and apply them to further development.